CFD modeling of pulmonary drug delivery. - Sin, Jasper Tuck Seng. (2009)
The lung has been studied as a possible route of administration for the treatment of systemic diseases. It provides direct access to disease in the treatment of respiratory diseases, while providing an enormous surface area and a relatively low enzymatic, controlled environment for systemic absorptions of medications. Pulmonary drug delivery has the advantage that it can deliver drugs directly to the region of therapeutic treatment, hence requiring lower medicine doses. The oral and nasal airways are forms of entry into the human respiratory tract. Resistance through the oral airways is much lower as compared to the nasal airways and thus, aerosol drugs are often delivered through inhalation via the oral airways. The purpose of this study was to investigate the effects of inhalation rate and particle size on the deposition in the human airway. Computational fluid dynamics (CFD) simulations of airflow and particle deposition was conducted for particle size ranging from 5μm to 100μm, and inhalation rates ranging from 30l/min to 60l/min. Laminar, multiphase mixture model was used and the forces included in the simulation are drag and gravity. Deposition occurs mainly by inertial impact and generally increases with the increase in inhalation rate and particle size.